What can we learn from over a decade of testing bats in New South Wales to exclude infection with Australian bat lyssaviruses?. Issue 4 (18th January 2022) - O'Connor, TW; Finlaison, DS; Kirkland, PD
Abstract : Australian Bat lyssaviruses (ABLV) are known to be endemic in bats in New South Wales (NSW), Australia. These viruses pose a public health risk because they cause a fatal disease in humans that is indistinguishable from classical rabies infection. All potentially infectious contact between bats and humans, or between bats and domestic animals, should be investigated to assess the risk of virus transmission by submitting the bat for testing to exclude ABLV infection. The aim of this study was to establish the prevalence of ABLV infection in bats submitted for testing in NSW and to document any trends or changes in submission and bat details. We examined all submissions of samples for ABLV testing received by the NSW Department of Primary Industries Virology Laboratory for the 13‐year period between 1 May 2008 and 30 April 2021. Fifty‐four (4.9%) ABLV‐infected bats were detected, with some clustering of positive results. This is greater than the prevalence estimated from wild‐caught bats. All bats should be considered a potential source of ABLV. In particular, flying‐foxes with rabies‐like clinical signs, and with known or possible human interaction, pose the highest public health risk because they are more likely to return a positive result for ABLV infection. This review of ABLV cases in NSW will help veterinarians to recognise the clinical presentations of ABLV infection in bats and emphasises the importance of adequate rabies vaccination for veterinarians.